Studi Pengaruh Perlakuan KOH Terhadap Kekuatan Tarik Komposit Serat Rami - Lado, Putra E.; Adoe, Dominggus G. H.; Pah, Jack C.A. (LONTAR Jurnal Teknik Mesin Undana (LJTMU ), 2023)
Currently, natural fiber composites have become the main choice for several industrial applications in the world. The strength of natural fibers such as hemp is based on laboratory results of mechanical strength testing which show that hemp has very suitable properties as a reinforcing composite for prosthetic socket materials. The tensile test is a mechanical stress-strain test that aims to determine the strength of a material against tensile forces. In the test, the test material is pulled until it breaks. Tensile testing is carried out to look for stress and strain (stress-strain test). From this test, we can know some of the mechanical properties of materials that are needed in engineering design. The results of research conducted on the study of the effect of KOH treatment on the tensile strength of hemp fiber composites show three things. First, the highest tensile stress value in hemp fiber was found in the 2% KOH treatment with a long soaking time of 2 hours with a value of 25.3 MPa. Second, the lowest tensile strain value in hemp fiber was found in the 6% KOH treatment with a long soaking time of 2 hours with a value of 0.1%. Third, the highest modulus of elasticity in hemp fiber was found in 6% KOH treatment with a 1-hour soaking time with a value of 47.1 MPa